KEAKURATAN KODE DIAGNOSIS PADA LEMBAR RINGKASAN MASUK DAN KELUAR PASIEN OBSTETRI DAN GINEKOLOGI DI RUMAH SAKIT PANTI RAPIH YOGYAKARTA - , BRIANNE RESTUSA VALENSIA, Nuryati, S.Far. MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: coding has an important role in the management of the hospital. Accuracy in coding disease will affect the report to be made by the hospital. Medical record if the quality is said medical records are accurate, complete, and reliable, valid and timely. One form of treatment in the medical record is a documentation and coding (coding) diagnosis. Through a preliminary study of 30 diagnoses of data entry on a summary sheet out of obstetrics and gynecology patients by 20% obtained results are not in accordance with the diagnosis code ICD 10. Objective: Knowing the diagnosis coding implementation on a summary sheet in and out patient obstetrics and gynecology, determine the percentage of accuracy of diagnosis coding on a summary sheet in and out patient obstetrics and gynecology, and determine the factors that cause inaccuracies in diagnosis coding sheet entry quick exit obstetrics and gynecology patients. Methods: This study used a descriptive study with a qualitative approach. Research design used a study design cross sectional. Methods of data collection by observation, documentation studies and interviews. Subjects in this study is two coding clerk, two medical specialists in obstetrics and gynecology, and head of the medical record installation. Objects used by the researchers is inpatient medical record file of obstetrics and gynecology in 2012 as many as 2243 medical record file, and the obtained samples were obtained medical record file number of the sampled object of research is as much as 339 files. Results: Implementation of coding diagnoses on the summary sheet in and out patient obstetrics and gynecology in Medical Records Installation Panti Rapih Hospital Yogyakarta done by 2 medical record officer with a background 3 Diploma in Medical Record education and non-education background Medical Record, to two officers recoding ever training on coding and medical record management. Implementation of coding in Hospital Panti Rapih been computerized using the SIRS encoding menu, if the code is not found in the SIRS database encoding menu, then the implementation of the coding is done manually according to encoding steps on ICD-10 Volume 2 and then add the code into the program. Analysis of the accuracy of diagnosis coding results on a summary sheet in and out-patient obstetrics and gynecology, there is 44.56% which is in accordance with the code of ICD-10. Factors causing inaccurate diagnosis codes entered on the summary sheet out inpatient obstetrics and gynecology, namely: human factors (HR), update ICD-10, and have not done the evaluation. Keywords:Coding,accuracy,Inpatient.